Endoscopic Fundoplication: Effectiveness for Controlling Symptoms of Gastroesophageal Reflux Disease. Issue 3 (May 2017) - Ebright, Michael I.; Sridhar, Praveen; Litle, Virginia R.; Narsule, Chaitan K.; Daly, Benedict D.; Fernando, Hiran C.
Objective: Transoral incisionless fundoplication (TIF) is a completely endoscopic approach to treat gastroesophageal reflux disease (GERD). We previously reported our initial results demonstrating safety and early effectiveness. We now present an updated experience describing outcomes with longer follow-up. Methods: For a three-year period, TIF procedures were performed on 80 patients. Preoperative workup routinely consisted of contrast esophagram and manometry. PH testing was reserved for patients with either atypical symptoms or typical symptoms unresponsive to protonpump inhibitors (PPIs). Heartburn severity was longitudinally assessed using the GERD health-related quality of life index. Safety analysis was performed on all 80 patients, and an effectiveness analysis was performed on patients with at least 6-month follow-up. Results: Mean procedure time was 75 minutes. There were seven (8.75%) grade 2 complications and one (1.25%) grade 3 complication (aspiration pneumonia). The median length of stay was 1 day (mean, 1.4). Forty-one patients had a minimum of 6-month of follow-up (mean, 24 months; range, 6–68 months). The mean satisfaction scores at follow-up improved significantly from baseline ( P < 0.001). Sixty-three percent of patients had completely stopped or reduced their PPI dose. Results were not impacted by impaired motility; however, the presence of a small hiatal hernia or a Hill grade 2/4 valve was associated with reduced GERD health-related quality of life scores postoperatively. Conclusions: At a mean follow-up of 24 months, TIF is effective. Although symptoms and satisfaction improved significantly, many patients continued to take PPIs. Future studies should focus on longer-term durability and comparisons with laparoscopic techniques.